History of EISCAT – Part 1: On the early history of EISCAT with special reference to the Swedish part of it - B. Hultqvist (History of Geo- and Space Sciences, 2011)
The paper describes the early history of EISCAT, from the very first ideas and Nordic contacts in the late 1960s to the end of the main development phase, when the facility had become a very advanced and reliable research instrument and its users had developed full competence in the second half of the 1980s. The preparation of the ''Green Book'', the Beynon meeting in London in 1973 and the activities started there, the first EISCAT Council meeting, the ''technical period'' 1976–1981, the inauguration in 1981 and the decade of improvements in most of the 1980s are described as seen from the Swedish point of view.